2016
DOI: 10.1002/cbf.3211
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Formation in Primary and Metastatic Colon Cancer Cells at Hypoxia and Normoxia

Abstract: High glucose consumption and lactate synthesis in aerobic glycolysis are a hallmark of cancer cells. They can form lactate also in glutaminolysis, but it is not clear how oxygen availability affects this process. We studied lactate synthesis at various oxygen levels in human primary (SW480) and metastatic (SW620) colon cancer cells cultured with L-Ser and/or L-Asp. Glucose and lactate levels were determined colorimetrically, amino acids by HPLC, expression of AST1-mRNA and AST2-mRNA by RT-PCR. In both lines gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The literature showed butyrate is absorbed by rectal colon cells in special by the monocarboxylate transporters (MCT)-1 [44]. The butyrate absorption could be inhibited in tumour colonic cells, whereas MCTs are associated with the efflux and influx of lactate, which is increased in colon cancer cells [45]. Moreover, patients with intestinal bowel diseases display downregulation of bile acid uptake transporter [46], increased intestinal permeability, and disruption of intestinal barrier [47], demonstrating that bowel inflammation can alter digestion and nutrients uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The literature showed butyrate is absorbed by rectal colon cells in special by the monocarboxylate transporters (MCT)-1 [44]. The butyrate absorption could be inhibited in tumour colonic cells, whereas MCTs are associated with the efflux and influx of lactate, which is increased in colon cancer cells [45]. Moreover, patients with intestinal bowel diseases display downregulation of bile acid uptake transporter [46], increased intestinal permeability, and disruption of intestinal barrier [47], demonstrating that bowel inflammation can alter digestion and nutrients uptake.…”
Section: Discussionmentioning
confidence: 99%
“…As a further contrast, a comparison of tumor tissue with non-tumor esophageal tissue failed to identify the increase in glycolytic intermediates [156] that would be anticipated by the scenario in Figure 3. Although it is generally thought that most lactate is derived from glycolysis [109,157,158], Figure 3 also does not consider that lactate can be derived from the metabolism of glutamine or serine [158][159][160][161][162][163][164]. Therefore, although Figure 3 offers an explanation that circumvents the apparent paradox introduced by M 2 PYK "inhibition" vs. increased lactic acid production, the entire assumption of the M 2 PYK inhibition is what should be questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, oxygen deficit is not necessarily a determinant of reduced cancer cell proliferation. During hypoxia, the concentration of building and energy compounds in the tumour environment decreases [53]. Thus, it can be concluded that low oxygen concentration is a signal for the adaptation of cellular metabolism to the simultaneous deficiency of energy and building blocks compounds.…”
Section: The Metabolic Heterogeneity Of Cancer Is Due To the Difficult Conditions 61 Effect Of Hypoxia On Metabolismmentioning
confidence: 99%